Exposure to liquid sweetness in early childhood: artificially‐sweetened and sugar‐sweetened beverage consumption at 4–5 years and risk of overweight and obesity at 7–8 years. Issue 12 (6th April 2018) - Macintyre, A. K.; Marryat, L.; Chambers, S.
Summary: Background: A significant gap exists in longitudinal evidence on early exposure to artificially sweetened beverages (ASBs) and weight outcomes for paediatric populations. Objective: The objective of this study is to examine the relationship between ASB/sugar‐sweetened beverage (SSB) consumption at 4–5 years and risk of overweight and obesity at 7–8 years. Methods: Data from a nationally representative cohort ( n = 2986) in Scotland were analysed using logistic regression to evaluate the association between exposure to ASBs/SSBs at 4–5 years and risk of overweight and obesity at 7–8 years. Results: There were positive unadjusted associations between ASB consumption and risk of obesity, and following adjustment for confounders, ASB associations attenuated, and only the middle consumption category (1 to 6 times per week) remained significant (odds ratio 1.57, 95% confidence interval CI 1.05–2.36). For SSB consumption, there were no significant unadjusted associations, and following adjustment for confounders, only the middle consumption category was significant (odds ratio 1.65, 95% CI 1.12–2.44). There were no significant associations for risk of overweight. Conclusions: Longitudinal analysis from 4–5 to 7–8 years demonstrated some evidence of associations between ASBs/SSB consumption and risk of obesity. However, non‐linear patterns and wide CIs suggest cautious interpretation and need for future studies with long‐term follow‐up.